Physicians' and nurses' attitudes regarding interprofessional collaboration in Cyprus - Gregoriou, Polyxeni; Papastavrou, Evridiki; Charalambous, Andreas; Rousou, Elena; Merkouris, Anastasios (My University, 2025)
A positive attitude between nurses and physicians toward interprofessional collaboration (IPC) enhances patient outcomes, job satisfaction, and the overall quality of healthcare services. This study aimed to examine the attitudes of physicians and nurses toward IPC in a public hospital and a private hospital in Cyprus. Data were collected using the Jefferson Scale of Attitudes Toward Nurse-Physician Collaboration questionnaire from a convenience sample of 573 healthcare professionals, including 79 physicians (13.8%) and 494 nurses (86.2%). The results showed that nurses had significantly more positive attitudes toward collaboration than physicians, with mean scores of 53.4 and 49.7, respectively (p < .001). Analysis of the four subscales revealed the following: Care vs. Treatment: Nurses reported higher positive attitudes compared to physicians (11 vs. 10, p < .001); Nurses' Autonomy: Physicians scored higher than nurses (11.3 vs. 10.9, p = .005); Physician Dominance: Nurses exhibited more positive attitudes than physicians (6.1 vs. 4.2, p < .001). Although both nurses and physicians demonstrated positive attitudes toward IPC, nurses appear more favorable to the concept. These findings underline the importance of integrating IPC-focused education into the training programs for both nurses and physicians, as this could foster more positive attitudes and ultimately enhance collaboration in healthcare settings.
Keywords: teamwork; Attitudes; interprofessional collaboration; nurse; physician; relationship